2022
DOI: 10.3390/children9030318
|View full text |Cite
|
Sign up to set email alerts
|

Needs and Research Priorities for Young People with Spinal Cord Lesion or Spina Bifida and Their Caregivers: A National Survey in Switzerland within the PEPSCI Collaboration

Abstract: The aim of this study was to describe the needs and research priorities of Swiss children/adolescents and young adults (from here, “young people”) with spinal cord injury/disorder (SCI/D) or spina bifida (SB) and their parents in the health and life domains as part of the international Pan-European Pediatric Spinal Cord Injury (PEPSCI) collaboration. Surveys included queries about the satisfaction, importance, research priorities, quality of life (QoL), and characteristics of the young people. Fifty-three surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Multi-disciplinary teams, comprising doctors, nurses, and physical therapists, play a pivotal role in making informed decisions regarding SCI and stoma formation. These decisions are based on a combination of existing literature evidence ( Allin et al, 2020 ; Benninger et al, 2022 ; Küçükakça Çelik & Taylan, 2023 ; McColl et al, 2012 ), their collective experience, and the preferences and wishes of the patients. However, not all SCI-affected individuals receive adequate information.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-disciplinary teams, comprising doctors, nurses, and physical therapists, play a pivotal role in making informed decisions regarding SCI and stoma formation. These decisions are based on a combination of existing literature evidence ( Allin et al, 2020 ; Benninger et al, 2022 ; Küçükakça Çelik & Taylan, 2023 ; McColl et al, 2012 ), their collective experience, and the preferences and wishes of the patients. However, not all SCI-affected individuals receive adequate information.…”
Section: Discussionmentioning
confidence: 99%
“…A study on various aspects of caregivers' lives showed age and educational status have a significant relationship among them [ 26 ]. In contrast, caregivers' educational attainment varied considerably in terms of proportions at the higher education level [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the rehabilitation concept has shifted towards a more patient-centered approach. There is evidence to suggest that including patients and caregivers in a study may improve its quality and ensure its applicability and usefulness [ 33 ]. In this regard, caregivers need additional continuing education and training programs on PI prevention and care that may influence positive attitudes and eventually result in successful PI prevention and care practice.…”
Section: Discussionmentioning
confidence: 99%